PENGARUH TUNJANGAN PROFESI GURU TERHADAP KINERJA YANG DIMEDIASI OLEH KOMPETENSI DI SMPN DISTRIK SENTANI KABUPATEN JAYAPURA - Meini Senewe; Bambang Supriyono; I Gede Eko Putra Sri Sentanu (Jurnal Administrasi Publik, 2022)
The study aims to: determine the effect of the teacher’s professional allowance on junior high school teachers performance mediated by competence. This research uses a quantitative approach with explanatory research. A total of 68 respondents was chosen at random from a pool of 85 teachers. Data were collected using a previously validated authoritative questionnaire. Hypothesis testing using variance-based SEM is called Partial Least Square (PLS). The results showed that: the teacher professional allowance has a significant and positive effect on the performance of 0,584 the teacher's professional allowance has a significant and positive effect on the competence of 0.369. the competence has a significant and positive effect on the teacher's performance of 0.446. there is an effect of the teacher's professional allowance on competency-mediated performance of 0.261. As expected, the Jayapura Regency Education Department will collaborate with professional organizations to develop innovative programs that can encourage teacher competency development and increase the role of subject teachers' deliberation and teacher working groups.